Understanding the meaning of short-term, yiyeqing relationships and how they are formed: Implications for condom use in Liuzhou, China - Zhang, Nan (2014)
Yiyeqing (“one night love”, i.e., having sex only once with a non-commercial partner) has increased in China, concomitant with the increase in heterosexual transmission of STI/HIV. Our study explored how participants who had experienced yiyeqing (YYQ) understood these relationships and characterized YYQ’s links to sexual risk behaviors. We conducted in-depth interviews with 45 adults in Liuzhou, a city in southwest China, who had YYQ experience. We analyzed the findings using social construction to interpret the participants’ understandings of YYQ. Participants reported that they tend to select YYQ partners whom they trust, which is built through introductions from social connections and within entertainment venues, resulting in the belief that their partners are free of STI/HIV and do not require protected sex. As YYQ relationships become more common, understanding the nature of these relationships is critical for developing public health messages that convey the risks associated with sex in short-term relationships and the need for condoms.